Toward a process theory of entrepreneurial ecosystems - Spigel, Ben; Harrison, Richard (Strategic Entrepreneurship Journal, 2018)
Research Summary: Entrepreneurial ecosystems have recently emerged as a popular concept within entrepreneurship policy and practitioner communities. Specifically, they are seen as a regional economic development strategy that is based around creating supportive environments that foster innovative start‐ups. However, existing research on entrepreneurial ecosystems has been largely typological and atheoretical and has not yet explored how they influence the entrepreneurship process. This article critically examines the relationships between ecosystems and other existing literatures such as clusters and regional innovation systems. Drawing on this background, the article suggests that a process‐based view of ecosystems provides a better framework to understand their role in supporting new venture creation. This framework is used to explain the evolution and transformation of entrepreneurial ecosystems and to create a typology of different ecosystem structures. Managerial Summary: Entrepreneurial ecosystems are a new buzzword within research and managerial circles. They represent the types of cultural, social, economic, and political environments within a region that support high‐growth entrepreneurship. But current research does little more than look at successful ecosystems to identify best practices. This article examines what we know about entrepreneurial ecosystems and links them with existing theories like clusters and regional innovation systems. We argue that successful and unsuccessful entrepreneurship within an ecosystem generates critical entrepreneurial resources like investment capital, skilled workers, and entrepreneurial knowledge. This, in turn, supports future high‐growth venture creation. The types of resources available in an ecosystem and the ability of these resources to flow through social networks helps separate strong, well‐functioning ecosystems from weak, poorly functioning ones.